The Female brain mengungkap misteri otak perempuan Lovann Brizendine ; penerjemah, Meda Satrio ; penyunting, Ati Cahyani - BRIZENDINE, Lovann; Cahyani, Ati; Satrio, Meda (Ufuk Press, 2007)
352 hlm 20 cm